(Answered)-Given the grammar: E' -> E$ E -> E+E E -> E*E E -> (E) E -> a The - (2025 Updated Original AI-Free Solution

Discipline:

Type of Paper:

Academic Level: Undergrad. (yrs 3-4)

Paper Format: APA

Pages: 5 Words: 1375

Question

Given the grammar:

E'?-> E$

E?->?E+E

E?->?E*E

E?->?(E)

E?->?a


The above grammar is an ambiguous grammar and it is not an LR(1) grammar.

Build the LR(1) sets of items.

Build the LR(1) Parsing Table.

There are conflicts in the LR(1) parsing table sine it is not LR(1) as stated above.

Fix the problem by removing the conflicts in the parsing table. Justify each case and each step.

After solving the conflicts and the grammar becomes LR(1), Merge the states whose core items are identical and then build the LALR(1) parsing table.

Parse the sentence a*(a+a). Use the LALR(1) parsing table if its LALA(1) grammar, otherwise, use the LR(1) parsing table.